La “razón dinamética humanista” de Miró Quesada Cantuarias - Del Piélago Vásquez, Margareth (2020)
Reason continues being one of the great questions of philosophy, perhaps one of the great themes of the tireless search of human beings to explain reality more and more. It has also been seen — for a long time— in a split, enthroned and hypostasized way; to finally be rejected, as a spurious fruit that would have led to destruction in these modern times. What are the chances that Reason has today? Is the cycle of discussion about that one closed? What areas / functions and relationships can be established from it? The work of Miró Quesada, runs as the path to a theory of reason, which is interwoven with ethics and humanism, it is framed within an authentic Latin American philosophy and constitutes what we call the humanistic dynamethics reason (dynamic, ethical and humanistic reason), as an open, possible and incomplete system that, in the context of globality, opens the world to found, unfold, question, recreate other modes of relationality.